PERTANGGUNGJAWABAN PIDANA DESK COLLECTOR FINTECH ILEGAL SERTA PERLINDUNGAN TERHADAP KORBAN - Wening Novridasati; Ridwan Ridwan; Aliyth Prakarsa (JURNAL LITIGASI (e-Journal), 2020)
Product technology-based financial services (financial technology-fintech) have changed a lot patterns of behavior and patterns of human life. In addition to its many benefits, it also endangers and poses many risks. The emergence of illegal online loans and collections through unethical, intimidating, inhumane, and unlawful desk collectors has an impact on victims and their families in the form of psychological disorders, and / or physical threats, or even victims who end their lives. In addition, victims do not get their rights as victims of criminal acts in general. This study aims to examine the legal protection of victims for illegal online loan collection, and examine the criminal liability of illegal fintech desk collector that causes victims. By using a normative juridical approach, secondary data sources collected are then analyzed qualitatively, the research results are obtained as follows: (1) the act of the desk collector has violated the Information and Electronic Transaction Law, the desk collector is subject to absolute responsibility (strict liability), and if the business activities carried out by the company can also be used the vicarious liability approach as a corporate criminal liability; (2) forms of protection for victims in the form of victims are entitled to get restitution for illegal online loan collection, and victims are entitled to get protection based on the Witness and Victim Protection Law. Keywords: Criminal Liability, Legal Protection for Victims, Online Loans.